Application of 10 nm AgNPs on in vitro culture of iaa9-5 tomato mutant (Solanum lycopersicum cv. Micro-Tom) - Asmara Reva Firstasa; Mubarok Syariful; Widiastuti Ani; Matra Deden Derajat; Zulaika Enny; Jadid Nurul (BIO Web of Conferences, 2025)
Tomato (Solanum lycopersicum L.) is a horticultural crop widely cultivated in Indonesia. Some efforts have been conducted to improve the quality of the tomato plant through plant breeding and characterization of tomato mutants. One of tomato mutant, iaa9-5, has been developed and characterized for its horticultural potential. The tomato iaa9-5 was reported for its 32 bp of deletion in the IAA9 gene, resulting in good adaptability to high temperature. Nowadays, the use of nano-elicitors such as silver nanoparticles (AgNPs) through in vitro culture has become a new alternative for enhancing plant secondary metabolites. However, their effect on plant growth might varied depending on the species. This study aims to evaluate the effect of 10 nm AgNPs on the development of tomato iaa9-5 mutant in vitro. The axenic nodal segments were used as explants and subjected to a variety of AgNPs concentrations (0 μg/L, 12.5 μg/L, 30 μg/L, and 75 μg/L) in the MS medium. Our results showed that all treatments did not show any callogenesis response. Meanwhile, all treatments resulted in 100% of organogenesis response, except for the 75 μg/L of AgNPs treatment. In addition, AgNPs seemed to inhibit plant growth compared to the control plants. However, we noticed that AgNPs might potentially maintain the chlorophyll synthesis and enhance plant secondary metabolites. Even though, some phytochemical assay still needs to be performed.